DISSEMINATED TUNGIASIS IN PATIENT WITH MENTAL DISORDER TREATED IN THE BRAZILIAN AMAZON: A CASE REPORT - Maciel, Marcel Gonçalves; da Silva, Djane Clarys Baia; Gonzaga, Jordana Pereira; de Castro, Amaury Trindade; Araújo, João Paulo Alves; Maciel, Luiz Henrique Gonçalves; da Silva Almeida, Clodoaldo; Yakubu, Michael Nosano (Seven Editora, 2025)
Tungiasis is a zooanthropophilic infection caused by the parasite Tunga penetrans. We report the case of a psychiatric patient, a Haitian migrant with disseminated tungiasis A 28-year-old Haitian man, HIV-negative and homeless in a city near Manaus, presented with crusty and pruritic lesions on his upper and lower limbs. Based on the characteristics of the lesions and the parasites collected, the patient was diagnosed with disseminated tungiasis by dermoscopy and histopathological examination. Subsequently, the parasite was identified as Tunga penetrans. The case reinforces the importance of surveillance of tungiasis even in endemic areas, such as Brazil and Haiti, particularly among individuals facing socioeconomic vulnerability and mental health disorders, as they may neglect hygiene and health practices, increasing the risk of severe infestations and disease progression.DOI: https://doi.org/10.56238/sevened2025.028-006